From Linear to Circular-Challenges for Changing Urban Metabolism?! An Analysis of Local Energy Transition Activities in Four European Cities. - Klindworth, Katharina; Djurasovic, Aleksandra; Knieling, Jörg; Säwert, Katja (Springer Fachmedien, 2017)
Challenges like climate change and peak oil are calling for a greater transformational process of urban regions. The vision of a regenerative and energy-efficient City with a high quality of life promotes an attractive future perception. The implementation requires changing urban metabolism from linear to circular. Promoting regional transformation encompasses creating new governance structures and realizing comprehensive measures. Acting an a municipal level, participation of society is as crucial as the active involvement of local actors and pioneers of vision. Changes of societal, political and economic framework conditions are strongly linked to an increase of individual awareness, activation of available resources and social learning processes. The paper outlines local transition processes of implementing this vision in four case study cities.
Keywords: Stadt; Resilienz; Transformation; Nachhaltigkeit; Stadtentwicklung; Anpassung; Klimawandel; Energie; Energiesystem; Städtevergleich; Internationaler Vergleich